2012
DOI: 10.5714/cl.2012.13.2.130
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and capacitance behaviors of cobalt oxide/graphene composites

Abstract: In this study, cobalt oxide (Co 3 O 4 )/graphene composites were synthesized through a simple chemical method at various calcination temperatures. We controlled the crystallinity, particle size and morphology of cobalt oxide on graphene materials by changing the annealing temperatures (200, 300, 400 o C). The nanostructured Co 3 O 4 /graphene hybrid materials were studied to measure the electrochemical performance through cyclic voltammetry. The Co 3 O 4 /graphene sample obtained at 200 o C showed the highest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 14 publications
(15 reference statements)
0
10
0
Order By: Relevance
“…Graphene addition has aided in circumventing the drawbacks faced by pristine cobalt oxide. Obtained specific capacitance is higher than rGO/Co 3 O 4 composite (291 F/g at 1 A/g) prepared by homogeneous incorporation of reduced graphene oxide sheets in cobalt oxide matrix reported by Wang et al [15], while Park et al [39] prepared Co 3 O 4 -GNS exhibited 396 F/g at 5 mV/s scan rate, Zhou et al [40] derived Co 3 O 4 -reduced graphene oxide scrolls demonstrated only 159.8 F/g at 5 mV/s scan rate and rapid microwave assisted synthesized graphene nanosheet/Co 3 O 4 composite prepared by J. Yan et al shows 243.2 F/g at 10 mV/s in 6 M KOH electrolyte [41]. High capacitance was due to the synergistic combination of good electro-activeness of cobalt oxide and high electrical conductivity of graphene nanosheets.…”
Section: Morphological Studiesmentioning
confidence: 83%
“…Graphene addition has aided in circumventing the drawbacks faced by pristine cobalt oxide. Obtained specific capacitance is higher than rGO/Co 3 O 4 composite (291 F/g at 1 A/g) prepared by homogeneous incorporation of reduced graphene oxide sheets in cobalt oxide matrix reported by Wang et al [15], while Park et al [39] prepared Co 3 O 4 -GNS exhibited 396 F/g at 5 mV/s scan rate, Zhou et al [40] derived Co 3 O 4 -reduced graphene oxide scrolls demonstrated only 159.8 F/g at 5 mV/s scan rate and rapid microwave assisted synthesized graphene nanosheet/Co 3 O 4 composite prepared by J. Yan et al shows 243.2 F/g at 10 mV/s in 6 M KOH electrolyte [41]. High capacitance was due to the synergistic combination of good electro-activeness of cobalt oxide and high electrical conductivity of graphene nanosheets.…”
Section: Morphological Studiesmentioning
confidence: 83%
“…Graphene, a carbon material with a two-dimensional nanostructure, has attracted a great deal of attention because of its high surface area, electrical conductivity, optimal mechanical stiffness, and high chemical stability [1][2][3]. In electrochemical measurements, multilayer graphene (from two to ten or more) is considered to be the promising electrode material for supercapacitors [4].…”
Section: Introductionmentioning
confidence: 99%
“…Which shows specific capacitances of 273 F/g at a charge‐discharge density of 0.5 A/g 56 . The carbon coated cobalt oxide electrode materials reported by Kumar et al 57 exhibit a specific capacitance of 395 F/g at a scan rate of 5 mV/s and 90% capacitance retention over 2,000 cycles 57 ; cobalt oxide (Co 3 O 4 )/graphene composites 58 exhibited similar specific capacitance values (396 F/g). By adopting thermal reduction process, Ramesh et al 59 utilized equimolar stannous and cobalt precursor solutions with N‐doped graphene oxides to afford SnO 2 @Co 3 O 4 /NGO composites.…”
Section: Resultsmentioning
confidence: 83%